Louvred Noise Barrier for Traffic Noise Reduction - Tomas Astrauskas; Pranas Baltrėnas; Tomas Januševičius; Raimondas Grubliauskas (The Baltic Journal of Road and Bridge Engineering)
Environmental issues near roads become more and more important in our society daily life. One of the most critical environmental issues is traffic noise. The present paper study louvred noise barrier designed by authors. The louvred noise barrier provides sound attenuation while allowing airflow and sunlight through it. Since the airflow resistance of the barrier is low, it requires a shallow foundation compared to conventional noise barriers. The sound attenuation performance of the louvred noise barrier was tested experimentally in a sound transmission chamber. Airflow resistance simulated using a computational fluid dynamics model. The simulation and experimental study were done with different louvred noise barrier setup: change of louvre blade angle and sound-absorbing material thickness. The results showed potential for future development for the field testing. Sound attenuation was highest in 2500 Hz and 3150 Hz octave frequency bands. Depending on the louvred barrier setup, sound attenuation was up to 28 dB(A) in mentioned frequency bands. The equivalent sound pressure level reduced up to 17 dB(A). The results showed that an increase in the louvre blade angle increases sound attenuation and increases airflow resistance.